“Onomastic Emphasis” in Julia Álvarez's Saving the World - April D Marshall (Names, 2009)
Abstract In her 2007 novel, Saving the World, Julia Álvarez uses alternating chapters to narrate both a modern tale and a corresponding historical saga. She employs nomenclature emphatically on multiple levels in the work in order to make the theme of identity central to the narrative. This study will examine the connection between name and character in Álavarez's novel. At the same time, it will also analyze the link between that connection and the various onomastic elements that serve to unite and even blend the two parallel stories.